The Challenge of Curriculum Integration for Islamic Universities: Setting the Principles of Curriculum Integration - Rufai, Saheed Ahmad (IIUM Journal of Educational Studies, 2016)
The Muslim world has witnessed remarkable developments in its educational system in the last four decades. Such developments include the founding of schools, establishment of universities, publication of journals, and organization of conferences and production of books, for the purpose of Islamization. It is obvious that knowledge is central to all these Islamizing initiatives as its integration is fundamental to the entire process of Islamization. Consequently, there are contributors to the curriculum integration level of Islamization by Muslim scholars across the world who have attempted to Islamize knowledge in their various areas. However, there is little attention to the professional requirements for integration of knowledge for Islamization especially at the university level. That informed the question, whose job is it to integrate the curriculum for Islamic universities? The purpose of this paper is to address this question. Utilizing a combination of the analytical method and creative synthesis, this paper is grounded in the scholarship of pragmatist philosophical foundations of the curriculum. It is hoped to provide guiding principles to the practice of integrating knowledge for Islamization. Such principles for curriculum development for Islamic universities, may also curb the growing trend of curriculum integration without the requisite professional curriculum-making considerations, portraying the Islamization of Knowledge (IOK) project as unsystematic.